Evolution of electroencephalogram in infants with tuberous sclerosis complex and neurodevelopmental outcome: a prospective cohort study. (2nd October 2021) - De Ridder, Jessie; Kotulska, Katarzyna; Curatolo, Paolo; Jansen, Anna C; Aronica, Eleonora; Kwiatkowski, David J; Jansen, Floor E; Jóźwiak, Sergiusz; Lagae, Lieven; ,
Abstract : Aim: To describe the evolution of electroencephalogram (EEG) characteristics in infants with tuberous sclerosis complex (TSC) and the relationship with neurodevelopmental outcome at 24 months. Method: Eighty‐three infants were enrolled in the EPISTOP trial and underwent serial EEG follow‐up until the age of 24 months (males n =45, females n =37, median age at enrolment 28d, interquartile range 14–54d). Maturation of the EEG background and epileptiform discharges were compared between the TSC1 and TSC2 variants and between preventive and conventional groups respectively. Results: Children with TSC2 more frequently had a slower posterior dominant rhythm (PDR) at 24 months (51% vs 11%, p =0.002), a higher number of epileptiform foci (median=8 vs 4, p =0.003), and a lower fraction of EEGs without epileptiform discharges (18% vs 61%, p =0.001) at follow‐up. A slower PDR at 24 months was significantly associated with lower cognitive (median=70 vs 80, p =0.028) and motor developmental quotients (median=70 vs 79, p =0.008). A higher fraction of EEGs without epileptiform discharges was associated with a lower probability of autism spectrum disorder symptoms (odds ratio=0.092, 95% confidence interval=0.009–0.912, p =0.042) and higher cognitive ( p =0.004), language ( p =0.002), and motor ( p =0.001) developmental quotients at 24 months. Interpretation: TSC2 is associated with more abnormal EEG characteristics compared to TSC1, which are predictive for neurodevelopmental outcome.